Date-Pit Arabinoxylan Oligosaccharides with Lactobacillus rhamnosus GG Mitigate Dual-Hit Injury from Proteus Mirabilis and Benzalkonium Chloride in MDCK Kidney Cells: A Real-Time qPCR Study - Ali Alsadoon, Hanoaf Shugaa (American Journal of Biology and Natural Sciences, 2026)
Arabinoxylan oligosaccharides (AXOS) have demonstrated certain promising bioactivities such as enhancing epithelial protected-ness and improving the probiotic-host interactions. Two of the toxicants of concern in the field of medicine, and that can potentially produce dual-hit renal epithelial injuries through oxidative stress, destabilization of the membranes, and transcriptional dysregulation, are Proteus mirabilis and benzalkonium chloride (BAC). The current research set out a venture to analyze the extent of protection offered by AXOS in the presence of Lactobacillus rhamnosus GG (LGG) against the cytotoxicity caused by P. mirabilis and BAC on MDCK renal epithelial cells, focusing mechanically on the inflammation and barrier-pertaining gene expression through the implementation of real-time quantitative polymerase chain reaction (qPCR). MDCK monolayers were pre-treated with AXOS (200 µg/mL) and LGG (1×10⁸ CFU/mL) prior to which, they were exposed to P. mirabilis (1×10⁶ CFU/mL) and BAC (20 µg/mL). The study measured cell viability, cell morphological changes, and the cell’s ability to transcriptionally control several genes such as TNF-α, IL-6, IL-8, occludin, claudin-1, and ZO-1. In the dual-hit exposed sample, there was a considerable surge in proinflammatory cytokines (3.8–6.2-fold; p < 0.01) with concomitant increases in the loss of tight junctions (2.5–4.1-fold; p < 0.01) which indicated that there was a major breakdown of the epithelial layers. The combination of AXOS and LGG cotreatment almost completely compensates for this defect and restores occludin, claudin-1, and ZO-1 expression close to its original levels. Furthermore, the cytokines were suppressed by 60–75%, and the monolayers were more intact with less cell detachment in the AXOS and LGG-treated groups. The strength of the protective effects of the AXOS and LGG combination vs. the protective effects of AXOS alone (p < 0.05). In conclusion, date-pit AXOS act synergistically with L. rhamnosus GG to confer significant cytoprotective and immunomodulatory effects, thereby attenuating dual-hit epithelial injury damage from P. mirabilis and BAC. These findings support AXOS-probiotic combinations to be pioneered as postbiotic therapies for the protection of renal epithelia.